Advancing Glycyrrhiza glabra L. Cultivation and Hairy Root Transformation and Elicitation for Future Metabolite Overexpression - Negin Afsharzadeh; Renate Paltram; Arne Jungwirth; Leila Tabrizi; Vahideh Nazeri; Hadi Kalantari; Heidi Halbwirth; Leila Samiei; Hester Sheehan; Majid Shokrpour (Horticulturae)
The production of valuable bioactive compounds in the medicinal plant Glycyrrhiza glabra L. (G. glabra) would benefit from biotechnological approaches for the cultivation and induction of metabolite-producing hairy roots. Germination trials were tested to overcome seed dormancy, achieving high germination rates with sulfuric acid treatment. Hairy root cultures of cotyledons using Rhizobium rhizogenes strain 1724 showed the highest transformation efficiency. A fast-growing line, line S, was subsequently exposed to light treatments (red, blue, and blue and red combined) to evaluate their effects on growth, phenolic content, and Ferric Reducing Antioxidant Power (FRAP). Hairy root cultures grown in blue light and in blue and red light combined had higher growth rates than those grown in red light only or in control conditions (dark). FRAP increased over time under all light treatments, including the control, and those cultures exposed to blue and red light combined had higher FRAP than the control. These findings provide valuable insights into conditions for optimal seed germination and hairy root transformation. Treatment of the line S with different qualities of light induced changes in antioxidant capacity and phenolic content, indicating promise for its use in upregulating secondary metabolite production in G. glabra for future biotechnological applications.